Mössbauer spectroscopy of iron compounds present in uranium containing sandstones. - Frank, E.; Labenski, F.; Saragovi- Badler, C. (Akadémiai Kiadó (Academia de Ciencas de Hungría), 1973)
Fil: Frank, E. Comisión Nacional de Energía Atómica; Argentina